Implementasi Reward dan Punishment dalam Meningkatkan Motivasi Belajar Peserta Didik di MIN 6 Desa Sinar Rejeki Jati Agung Lampung Selatan - Aska Mustika Asri; Sri Wahyuningsih; Latifatul Khoiriyah (Journal on Education, 2024)
The point of this specialist is to depict understudy learning inspiration utilizing the prize and discipline learning technique at MIN 6 Sinar Rejeki Jati Agung, South Lampung Rule. This exploration utilize desciptive subjective methodology. The information assortment strategies that specialists will utilize are perception, meetings and documentation. Information assortment strategies are precise and standard systems for getting the expected information. In view of the examination, it tends to be reasoned that the execution of discipline at MIN 6 Sinar Rejeki Jati Agung can be said to have been executed and done well. Instructors have understood that the discipline given isn't expected to hurt or harm understudies. Nonetheless, to shield understudies from botches made or not, instructors apply disciplines that are instructive and useful, as well as to build interest or increment understudies' learning inspiration. Right now, understudies actually believe discipline to be an activity pointed toward troubling or in any event, harming understudies. This is on the grounds that there were disciplines given by past educators or instructors who didn't know about the guidelines for giving discipline. The positive effect of executing this discipline is that it assists educators with safeguarding understudies from defying the norms, however on the off chance that they disrupt the guidelines, the discipline can make a hindrance difference and give an example to understudies. In the mean time, that's what the adverse consequence is assuming the discipline is applied erroneously, it will create continuous issues for educators, understudies and guardians. The component that upholds the execution of this discipline is collaboration between educators, guardians and school chiefs. Since their authorization to rebuff understudies is the main variable. What's more, the restraining factors likewise come from school chiefs, guardians and understudies. Since, in such a case that there is no participation and consent from the school head and guardians, the educator will be hampered in giving discipline since there is strain from the two of them. Educators are likewise a repressing variable, since instructors don't have the information to give discipline.